2012
DOI: 10.36834/cmej.36587
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles of medical students change along the study program: from ‘thinking and watching’ to ‘thinking and doing’

Abstract: Background: Most students admitted to medical school are abstract-passive learners. However, as they progress through the program, active learning and concrete interpersonal interactions become crucial for the acquisition of professional competencies. The purpose of this study was to determine if and how medical students' learning styles change during the course of their undergraduate program. Methods: All students admitted to the Pontificia Universidad Católica de Chile (PUC) medical school between 2000 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…Teaching methods that include practice with patients in real situations may also have promoted a more active learning style [ 5 ]. A similar difference in learning styles between preclinical and clinical students was also observed in a recent study from Spain [ 4 ]. Previous research, from various settings, has found that some learning styles, such as theoretical, reflective, and assimilative, were likewise more commonly found in preclinical students [ 6 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Teaching methods that include practice with patients in real situations may also have promoted a more active learning style [ 5 ]. A similar difference in learning styles between preclinical and clinical students was also observed in a recent study from Spain [ 4 ]. Previous research, from various settings, has found that some learning styles, such as theoretical, reflective, and assimilative, were likewise more commonly found in preclinical students [ 6 ].…”
Section: Discussionsupporting
confidence: 83%
“…The preclinical curriculum focuses on basic knowledge of medical sciences, which involves numerous complex details. As a result, the teaching methods unavoidably involved didactic lectures [ 4 ]. In our setting, the teaching methods used for preclinical students included lectures, problem-based learning, self-directed learning, and written reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The learning styles of students have been shown to change as the student progresses in their academic years (12). The findings from another study suggest that the theoretical lectures and practical sessions of the preclinical training years (first-and secondyear) exhibit assimilating learning style (13,14).…”
Section: Discussionmentioning
confidence: 99%